Correlation between Socioeconomic Level and Nutritional Status with The Incidence of Helminthiasis in Elementary Students - Rahmah, Maulida; Nurhayani, N; Bestari, Rochmadina Suci; Tolibin, Restu Triwulandani; Najmii, Muhammad Firoos Allaam (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: To examine the relationship between socioeconomic status and nutritional condition with the prevalence of helminthiasis among students at SDN 02 Selokaton. Methodology: This research employs a quantitative observational analytic approach with a cross-sectional design. A total of 130 fifth- and sixth-grade students were selected using total sampling. The independent variables (socioeconomic status and nutritional status) were assessed through questionnaires and anthropometric measurements, respectively. The dependent variable, helminth infection incidence, was determined through microscopic stool analysis. Data were analyzed using Spearman's test. Results: Among the 65 students who met the inclusion criteria, 20% (13 students) tested positive for helminth infections. Poor nutritional status was found in 6.2% of students, while 43.1% had low nutritional status. Most students came from families with a middle socioeconomic status (78.5%). No significant correlation was found between socioeconomic status or nutritional status and the incidence of helminth infections (p > 0.05). Applications/Originality/Value: Despite the lack of a significant correlation, the high prevalence of helminth infections suggests that factors like environmental hygiene and hygienic behaviors may play a more influential role. Health education and improved sanitation are needed to reduce the prevalence of helminth infections in the area.